2005
DOI: 10.1002/pmic.200402111
|View full text |Cite
|
Sign up to set email alerts
|

Extending ribosomal protein identifications to unsequenced bacterial strains using matrix-assisted laser desorption/ionization mass spectrometry

Abstract: A protocol has been developed that allows protein identifications using available DNA-based or protein sequences from a reference strain of a bacterial species to be extended to bacterial strains for which no prior DNA-based or protein sequence information exists. The protocol is predicated on careful isolation of a specific sub-cellular group of proteins. In this study, ribosomal proteins were chosen due to their high relative abundance and similarity in copy number per cell. After isolation of ribosomal prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 35 publications
4
67
0
1
Order By: Relevance
“…We examined the modification states of several S12 mutants of T. thermophilus IB-21 (ATCC 43815) (16) by MALDI-TOF MS as described previously (23). Wild-type S12 was determined to have a mass of 14,519 Ϯ 6 Da (Table 1), consistent with our previous report (24), indicating loss of the initial methionine and the presence of the ␤-methylthiolation. Considering the proximity to D88, we sought to determine if the streptomycinresistant mutants K87R and K87E (12) were modified at D88.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…We examined the modification states of several S12 mutants of T. thermophilus IB-21 (ATCC 43815) (16) by MALDI-TOF MS as described previously (23). Wild-type S12 was determined to have a mass of 14,519 Ϯ 6 Da (Table 1), consistent with our previous report (24), indicating loss of the initial methionine and the presence of the ␤-methylthiolation. Considering the proximity to D88, we sought to determine if the streptomycinresistant mutants K87R and K87E (12) were modified at D88.…”
supporting
confidence: 52%
“…2A), near the streptomycin binding site and in the midst of residues altered in streptomycin-resistant mutants (14). This modification has also been found to occur in the phototrophic bacterium Rhodopseudomonas palustris (22), and we have identified it for the extremely thermophilic bacterium T. thermophilus (24). Posttranscriptional modifications of rRNA residues have been shown to affect resistance to various antibiotic classes (reviewed in reference 8).…”
mentioning
confidence: 74%
“…Intact proteins were assigned by accurate mass measurement of the ribosome mixture before proteolysis (T = 0 min) and by comparison to protein molecular weights predicted for T. thermophilus HB8 from entries in the SwissProt database as before [42]. The r-proteins L1, L2, L3, L6, L13, L14, L15, L16, L17, L18, L20, L21, L22, L23, L24, L28, L29, L30, L32, L33, L34, L35, and L36 of the large subunit, and rproteins SThx, S6, S8, S9, S10, S14, S15 and S17 of the small subunit were still detected as intact proteins even after incubation with either trypsin or Proteinase K for 1500 min.…”
Section: Limited Proteolysis Of T Thermophilus 70s Ribosomesmentioning
confidence: 99%
“…Proteomic studies of bacterial ribosomal proteins have reported di-or monomethylation at this residue in E. coli (29), Caulobacter crescentus (28), and Rhodopseudomonas palustris (27), and the reported molecular mass of Thermus thermophilus RpL7/L12 also suggests methylation (26). However, this modification appears not to be present in all bacteria as Bacillus subtilis RpL7/L12 was found to be unmodified (45).…”
Section: Discussionmentioning
confidence: 99%